The Effect of Substance Abuse on Domestic Violence: Pengaruh Penyalahgunaan Narkoba terhadap Kekerasan Dalam Rumah Tangga - Alhussein, Zahraa Ali Abed; Alwan, Eman Hussien (Psikologia : Jurnal Psikologi, 2024)
find out the relationship between drug abuse and domestic violence . descriptive study design. A sample of (50) couples were introduced. A two questionnaire self-report w used to gather data from drug users and abused women .data were gathered in 2024 between January and March The results indicate that the average age of the male is 27±4, then 24 ±4 female, are married, and (38%) were graduated from secondary school while 36% of their wives are graduated from intermediate schools. 82% of clients with substance use are working with free works while 78% of their wives are housewives. 42% of participants are within monthly income of 601000 – 900000 Iraqi dinars. 60% of wives betrayed by their clients with substance use problems. there is positive significant relationship between substance use among clients and domestic violence among their wives at p-value= .037.Among substance abuse and domestic violence are positive correlated, as shown by significant reverse correlation with p-valy67uue=. 037. Domestic abuse is prevalent and unacceptable in both lifetime and present times. Regardless of age, economic standing, or educational attainment, women will at some point in their lives become victims of abuse. Abuse of drugs increases the chance of violence. Spreading the culture of the danger of drugs and treatment from them by opening rehabilitation centers in various cities and villages Focus on protecting women and developing work to protect them from the risk of violence in coordination with community police.